CIVIL DOCUMENT SERVICES THROUGH THE LOAKK (LAHIR OLIH AKTA KARO KK) PROGRAM IN TEGAL REGENCY, CENTRAL JAVA PROVINCE - Devi Yulianti Nabila; Romi Saputra; Rangga Zanuary; Fajar Eka Pangestu (Registratie, 2024)
Tegal Regency has an area of ​​87,878 hectares with the furthest districts from the government center being Warureja (30 km) and Bumijawa (28 km). As an approach in civil administration service, the Civil Pupulation and Registry Office of Tegal Regency provides the LOAKK (Lahir Olih Akta Karo KK) Program. This research aims to determine and analyze the civil document service through the LOAKK Program, inhibiting factors, and efforts made by the Tegal Regency Civil Registry Office in overcoming existing obstacles. This is a descriptive qualitative research with an inductive approach. The informants and respondents were selected using the purposive sampling technique and the data were collected using observation, interviews, and documentation. The data were analyzed using was reduction, presentation, and drawing conclusions, and then the data was validated using triangulation. Research results indicate that the civil document service through the LOAKK Program has been running for 5 (five) years, but there have been several obstacles from the community and the LOAKK Program staff. Keywords: Service, LOAKK Program, Civil Documents.